Study on coded distributed fast Hadamard transform based non-binary LDPC code decoding algorithm - Rui LIU; Yong LI (Tongxin xuebao)
Despite the excellent error correction performance and burst error resistance capability of non-binary LDPC codes, the complexity of the decoding algorithms hinders their broader application.In the classic FHT-QSPA decoding, the fast Hadamard transform (FHT) and its inverse transform (IFHT) have become the main bottleneck for updating the check nodes.Therefore, a coded distributed FHT scheme based on systematic MDS codes was proposed.In the scheme, the channel probability was modeled by the master node as a matrix and it was segmented, and those sub-matrices were encoded into redundant ones.Then, all the sub-matrices were offloaded to worker nodes to perform parallel FHT and IFHT, and the results were sent back to the master node for the final decoding.By embedding redundant information, the proposed scheme resolved the straggling problem, improving the efficiency, and accelerating the entire decoding process.Comparisons with other coded matrix multiplication schemes, the proposed scheme provides lower encoding complexity, higher numerical accuracy in decoding recovery, and maintains an efficient butterfly operation, effectively reducing the computational complexity of worker nodes.The time comparison and decoding performance analysis reveal that the proposed scheme achieves up to approximately 3.8 times acceleration compared to the traditional single-node FHT scheme, significantly enhances the FHT-QSPA decoding efficiency without affecting the decoding performance.